STUDY ON INFLUENCE OF PARASITIC OSCILLATIONS OF VIBRATOR MASS FLOW TRANSDUCER ON MEASUREMENT RESULTS - Gennady G. Parkhomenko (Advanced Engineering Research, 2012)
The parasitic oscillations of the vibrator mass flow transducer caused by the force point shift from the axis of symmetry of the U-tube are investigated. The defining formulas of the absolute and adduced additive errors are received. The criteria on reducing these errors in the flowmeter design are developed.